Management of Bilateral Ectopic Canines: A Case Report - Smruti Bhushan Nanda1 , Sumita Mishra2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
An ectopic canine tooth may originate due to genetic/environmental aberrations. These teeth demandcorrection as they can move in the jawbone and damage the adjacent bone, roots of the teeth, pose estheticconcerns. Timely diagnosis and treatment play a pivotal role. The case report stresses on an extractiontreatment approach for correction of ectopic canine in a patient posing severe crowding in both upper andlower arches